2015
DOI: 10.1007/s13277-015-3237-1
|View full text |Cite
|
Sign up to set email alerts
|

AZD-4547 exerts potent cytostatic and cytotoxic activities against fibroblast growth factor receptor (FGFR)-expressing colorectal cancer cells

Abstract: Colorectal cancer (CRC) causes significant mortalities worldwide. Fibroblast growth factor (FGF) receptor (FGFR) signaling is frequently dysregulated and/or constitutively activated in CRCs, contributing to cancer carcinogenesis and progression. Here, we studied the activity of AZD-4547, a novel and potent FGFR kinase inhibitor, on CRC cells. AZD-4547 inhibited CRC cell growth in vitro, and its activity correlated with the FGFR-1/2 expression level. AZD-4547 was cytotoxic and pro-apoptotic in FGFR-1/2-expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
10
0
1
Order By: Relevance
“…However, in our present study, the lowest IC50 for PD173074 was observed in the HCT116 cell line, which exhi-bits high FGFR1 expression. Furthermore, BGJ398 and AZD4547 are known to have a strong anti-proliferative effect in CRC cell lines with high FGFR1 expression [14,18]. Therefore, proper selection of a biomarker that can predict the res-ponses to FGFR-targeted therapy is muchneeded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our present study, the lowest IC50 for PD173074 was observed in the HCT116 cell line, which exhi-bits high FGFR1 expression. Furthermore, BGJ398 and AZD4547 are known to have a strong anti-proliferative effect in CRC cell lines with high FGFR1 expression [14,18]. Therefore, proper selection of a biomarker that can predict the res-ponses to FGFR-targeted therapy is muchneeded.…”
Section: Discussionmentioning
confidence: 99%
“…The FGFR1 copy number status in these five cell lines was confirmed by ddPCR, while the FGFR1 expression was confirmed by Western blot. The effect of FGFR inhibitor, PD173074, on cell proliferation was determined using the WST-1 assay in SNU-C1, and 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) cell viability assay in the other cell lines [18]. For the WST-1 assay, after the indicated treatment, 20 µL of WST-1 solution was added per well and the cells were incubated for 4 hours at 37°C.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…AZD4547 has shown promising in vitro results inhibiting cell growth in gastric cancer patient derived cell lines carrying the FGFR2 amplification; it demonstrated good anti-proliferative activity in an endometrial cell line harboring the FGFR2-K310R/N550K mutations. Furthermore, AZD4547 inhibited colorectal cancer cell growth with a high expression of FGFR1-2 with cytotoxic and pro-apoptotic effects (Kwak et al, 2015;Lu et al, 2008d;Yao et al, 2015). A phase II proof of concept study in patients with FGFR1 (HER2 negative breast cancer [BC]/NSCLC) and FGFR2 (gastroesophageal cancer [GC]) amplified tumors demonstrated that AZD4547 has a higher activity in FGFR2 amplified GC (RR 33%) compared to FGFR1 amplified BC (RR 12.5%) (Smyth et al, 2015).…”
Section: Azd4547mentioning
confidence: 99%
“…AZD4547 is a potent, oral, highly selective inhibitor of FGFR1–3 with proven antitumour properties from preclinical studies [1115], including work in FGFR2-amplified GC xenografts that demonstrated complete and prolonged tumour regression in several AZD4547-treated animals [12]. An initial Phase I study in a Western population indicated that AZD4547 monotherapy has an acceptable safety profile in patients with several tumour types (NCT00979134).…”
Section: Introductionmentioning
confidence: 99%